Laws of formation of spectra of noise in cabins of bridge cranes from influence of sources of air noise - S.A. RAZDORSKIY; I.E. VILINOV (Advanced Engineering Research)
Results of experimental researches in cabins of bridge cranes are resulted. Influence of sources on formation of a sound field in cabins is revealed.